+0  
 
0
87
1
avatar

sin2x-sqrt(3)*cosx=o

Guest Apr 18, 2017
Sort: 

1+0 Answers

 #1
avatar
0

Solve for x:
sin(2 x) - sqrt(3) cos(x) = 0

Expand trigonometric functions:
2 cos(x) sin(x) - sqrt(3) cos(x) = 0

Collecting terms, 2 cos(x) sin(x) - sqrt(3) cos(x) = (2 sin(x) - sqrt(3)) cos(x):
cos(x) (2 sin(x) - sqrt(3)) = 0

Split into two equations:
cos(x) = 0 or 2 sin(x) - sqrt(3) = 0

Take the inverse cosine of both sides:
x = π/2 + π n_1 for n_1 element Z
 or 2 sin(x) - sqrt(3) = 0

Add sqrt(3) to both sides:
x = π/2 + π n_1 for n_1 element Z
 or 2 sin(x) = sqrt(3)

Divide both sides by 2:
x = π/2 + π n_1 for n_1 element Z
 or sin(x) = sqrt(3)/2

Take the inverse sine of both sides:
x = π/2 + π n_1 for n_1 element Z
 or x = π - sin^(-1)(sqrt(3)/2) + 2 π n_2 for n_2 element Z or x = sin^(-1)(sqrt(3)/2) + 2 π n_3 for n_3 element Z

sin(2 x) - sqrt(3) cos(x) ⇒ sin(2 (π/2 + π n_1)) - sqrt(3) cos(π/2 + π n_1) = 0:
So this solution is correct

sin(2 x) - sqrt(3) cos(x) ⇒ sin(2 (329 π - sin^(-1)(sqrt(3)/2))) - sqrt(3) cos(329 π - sin^(-1)(sqrt(3)/2)) = 0:
So this solution is incorrect

sin(2 x) - sqrt(3) cos(x) ⇒ sin(2 (184 π + sin^(-1)(sqrt(3)/2))) - sqrt(3) cos(184 π + sin^(-1)(sqrt(3)/2)) = 0:
So this solution is incorrect

The solution is:
Answer: | x = π/2 + π n_1 for n_1 element Z          or x = π - sin^(-1)(sqrt(3)/2) + 2 π n_2 for n_2 element Z            or x = sin^(-1)(sqrt(3)/2) + 2 π n_3 for n_3 element Z

Guest Apr 18, 2017

4 Online Users

avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details